Supporting Individuals with Autistic Spectrum Disorder with Various Technologies: A Review - Naren, J.; Vithya, G.; Srivathsan, S.; Reddy, Bharath (International Journal of Psychosocial Rehabilitation, 2024)
Autism Spectrum Disorder (ASD) is a complex disorder that has become quite common in the recent years. Various research has shed light on the importance of disorder’s early detection and the much-needed support children with ASD need. The study assesses technologies as support tools for individuals with autism spectrum disorder. Real-life situations often create anxiety and panic attacks in individuals with ASD, as the disorder prevents them from acting and reacting normally. Technologies help create controlled environments, acting as an intervention to support people with ASD in therapies. The paper is divided into the types of technologies developed as support tools: mixed reality applications, dedicated applications, and robots. Each is further classified by the difficulties that are cantered on, namely communication and interaction skills, social learning and imitation skills, and other conditions. Most of the studies show that technology is a useful tool in supporting people with ASD. However, understanding that autism is a spectrum disorder and symptoms vary from one individual to another is essential, and the need for personalized support tools as opposed to generalized tools is necessary. In the above-mentioned way, there is an opportunity for such children to express themselves.